Peri-operative platelet function testing: The potential for reducing ischaemic and bleeding risks - Gurbel, Paul A.; Mahla, Elisabeth; Tantry, Udaya S. (Thrombosis and Haemostasis, 2011)
The pivotal role of platelet activation and reactivity during atherothrombotic event occurrence associated with acute coronary syndromes (ACS) or percutaneous coronary interventions (PCI) is well established. Numerous translational research studies have established a threshold level of platelet reactivity during dual antiplatelet therapy above which a higher risk for ischaemic event occurrence has been observed. The clinical validity of these threshold values in reducing ischemic event occurrence with modified P2Y12 receptor therapy is currently under investigation in large-scale clinical trials. The association between on-treatment platelet reactivity measured by an ex vivo assay and the occurrence of bleeding events is less established. Currently, there is limited evidence of an association between platelet inhibition and coronary artery bypass grafting (CABG)- related bleeding in patients on clopidogrel therapy indicating that preoperative platelet function monitoring may guide both the timing of elective CABG and the administration of blood products in patients needing surgery. However, in the absence of a large-scale prospective clinical trial, routine platelet function monitoring and modification of timing of surgery based on platelet function monitoring are currently not recommended.
Keywords: Atherothrombosis; antiplatelet drugs; platelet pharmacology